Si par un mal étrange est atteint un personnage - René Audet (Itinéraires)
This article studies the relationship between narrativity and fictionality in the highly metatextual novel Le Mal de Montano from Catalan writer Enrique Vila-Matas. Through this intertwined multi-layer fiction, a writer’s representation is build, coping with fictional incertainties, a diffracted narrative and lots of literary figures brought by the narrator as field of reference. Is shown the complexity of negociation between the fiction’s inner coherence and the path through different narratives, literary genres and the construction of the figure of the writer.